Prestasi Akademik Mahasiswa Saat Pandemi: Pengaruh Kompetensi Dosen dan Interaksi Mahasiswa Akuntansi Universitas Muara Bungo - Ronald N Girsang (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The Covid-19 pandemic not only has an impact on public health, but also has an impact on the world of education. This research examines the factors that influence the academic achievement of accounting students. Accounting lectures, which contain mostly calculation material, even though they are taught boldly, must be mastered by the students. This researcher tested whether lecturer competency variables and student interaction had an effect on the academic achievement of accounting students. With a sample size of 70 people, and using Partial Least Square, using Smart PLS 4.0 it was concluded that Competency. Lecturer competency partially influences the academic achievement of brave learning during the Covid-19 pandemic. Meanwhile, student interaction has no partial effect on the academic achievement of brave learning during the Covid-19 pandemic.